(untitled) (Indian Journal of Public Health Research & Development, 2023)
Abstract Background and objectives: The exact course of SARS -2(COVID-19) and its complications on multiorgan system are complex and still under studies. Musculoskeletal system has also been affected post covid in various forms. This study was taken up to analyse the effects of covid-19 disease on the hip bone and join tissue. Materials and Methods: Retrospective analysis of ten patients was done who had been hospitalised with covid-19 infection and later complained of hip pain. They underwent MR imaging and were found to have degenerative changes characterizing with avascular necrosis (AVN) of head of femur .One of them had history of previous surgery of femur with PFN, doin well but developed AVN after covid. Results: Observation of this group showed a clear correlation among the history of COVID-19 disease in the patients, moderately severe symptoms, high levels of IgG antibodies, and the time of occurrence of joint changes. No other risk factors for AVN or auto-immune or degenerative diseases were found in the study group. The group of patients responded well to empirical treatment with anti-inflammatory drugs ans supportive therapy, which subsided acute inflammatory symptoms and pain in the joints. Conclusions: It is concluded that there have been obvious musculoskeletal complications in covid patients including AVN which could be attributed to the high use steroids and microembolism leading to bone necrosis. Hence more studies and long follow-up is suggested.